Primary DLBCL of testis: Presenting as a case of testicular mass - Kuppusamy, Thilagarani; Prasad, Sowmya Devi Ajith (Indian Journal of Case Reports, 2022)
Primary testicular non-Hodgkin’s lymphoma (NHL) is a rare, clinically aggressive form of extranodal lymphoma and constitutes 1% of all NHL and 5% of all testicular neoplasms. The vast majority of primary testicular lymphomas (PTLs) are diffuse large B-cell lymphoma (DLBCL); however, Burkitt’s lymphoma, anaplastic lymphoma, or Hodgkin’s lymphoma may primarily involve the testis but it is less common. High inguinal orchiectomy, along with chemotherapy with or without radiotherapy, is the current treatment of choice for these tumors. Here, we present the case of primary testicular NHL in a 72-year-old male.